If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6.5x + -3 = 11 Reorder the terms: -3 + 6.5x = 11 Solving -3 + 6.5x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 6.5x = 11 + 3 Combine like terms: -3 + 3 = 0 0 + 6.5x = 11 + 3 6.5x = 11 + 3 Combine like terms: 11 + 3 = 14 6.5x = 14 Divide each side by '6.5'. x = 2.153846154 Simplifying x = 2.153846154
| 1-6x=5x+1 | | k-7=-12 | | -2(-2-4n)-4n=-2+5(n+3) | | -7x+5=115+3x | | 1-2x=7x+10 | | -12+x=23 | | 4x^2+2x+16=0 | | 3x+1=-19+x | | 4y*1*9*7y= | | 4g+13500=8500 | | 5x-4(-x+1)=-7 | | 3m-12=36 | | 14u-18v= | | n/9=18 | | 0.6x+11.4=x-5.32 | | 5(9+6x)+7=-12+14x | | -18+9a=8(1+a)-13 | | 10xy-4y= | | 12(v-13)=2v-66 | | 4t^2+24t-27=0 | | 24+y*2=x | | -25=4(5k-7)+3(1+3k) | | 6(2x+1)=12x+3 | | -2(1-10n)=-52+10n | | 48.3/17.3 | | -2(1-10n)=-27+14b | | 0.6x+1.43=x-6.22 | | 6(4b+2)+3b=-27+14b | | (2/3x)-4=5/6 | | 2/3x-4=5/6 | | 5x-25=2x-38 | | -26=4(8n+6)-2(3n-1) |